(untitled) - Patterson, James; 1947-; Paetro, Maxine (New York, NY, 2017)
Lindsay Boxer has a beautiful baby daughter and a husband she loves unconditionally. Always focused on her career as a San Francisco police detective, she wondered what domestic bliss might feel like, and shes never been happier. She cant imagine that a brutal murder at a downtown luxury hotel, and the disappearance of a gorgeous blond woman from the scene would have anything to do with her own life and marriage--yet Lindsay cant ignore disturbing clues that hit very close to home. When an explosive tragedy plunges San Francisco into chaos, Lindsay is pressed to investigate a criminal plot that stretches around the globe, and she again finds herself following signs that lead to her own front door. Fighting powerful enemies trying to protect their operatives and conceal the truth at all costs, Lindsay turns to the Womens Murder Club for help as she desperately searches for the elusive and deadly blonde...before she loses her husband for good.
Keywords: Fiction; Murder; Fiction; San Francisco; Investigation; Policewomen; Fiction; Womens Murder Club (Imaginary organization); California; San Francisco (Calif.); Fiction; Thrillers (Fiction); Detective and mystery fiction